2021
DOI: 10.3390/pathogens10020154
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Planta Studies on Temperature Adaptation of Exserohilum turcicum Isolates from Maize in Europe and South America

Abstract: Northern Corn Leaf Blight (NCLB) is a fungal leaf disease in maize caused by Exserohilum turcicum. NCLB occurs worldwide, from tropical to temperate zones raising the question about plasticity of temperature adaptation of local isolates of the pathogen. Seven isolates of E.turcicum originating from South America and seven from Europe were compared for their response to temperature variations in vitro and in vivo between 15 and 30 °C. In vitro, isolates originating from Europe and South America significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…A comparison of isolates of S . turcica from South America and Europe suggested that aggressiveness of NCLB on maize in cooler climate zones will increase with rising temperatures (Navarro et al, 2021). In addition, recent climate change, namely warmer weather conditions throughout the year (e.g., mild and moist winters supporting inoculum survival and reproduction on maize residues) may also have favoured leaf diseases in maize (Miedaner, 2018).…”
Section: Change In the Relative Importance Of Fungal Leaf Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of isolates of S . turcica from South America and Europe suggested that aggressiveness of NCLB on maize in cooler climate zones will increase with rising temperatures (Navarro et al, 2021). In addition, recent climate change, namely warmer weather conditions throughout the year (e.g., mild and moist winters supporting inoculum survival and reproduction on maize residues) may also have favoured leaf diseases in maize (Miedaner, 2018).…”
Section: Change In the Relative Importance Of Fungal Leaf Diseasesmentioning
confidence: 99%
“…For example, NCLB caused by S . turcica is at present the most troublesome leaf disease in European maize cultivation (Navarro et al, 2021), provided there is sufficient humidity for infection (Galiano‐Carneiro & Miedaner, 2017) during the growing season. There are qualitative and quantitative resistance sources; however, some of the qualitative, race‐specific Ht genes are already ineffective due to virulent pathogen populations.…”
Section: Leaf Disease Resistance Breeding Approachesmentioning
confidence: 99%
“…The disease is widely distributed and economically the most important foliar disease of maize [2,3]. The disease has a worldwide distribution predominantly in areas with 75%-90% relative humidity and 22°C-25°C temperature during the cropping season [4,5]. NCLB causes enormous damage to the maize crops, and grain yield losses range from 24% to 91% [6,7], depending on the growth stage of the crop at which infection occurs, the severity of the outbreak, the resistance of the host plant and the virulence of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…As the type species of Exserohilum , E. turcicum , a filamentous hemibiotrophic fungus, is notorious for causing northern corn leaf blight (NCLB) [3] , [5] . Of late years, this disease has become increasingly problematic worldwide with the extensive planting of susceptible varieties of maize in many countries [6] , [7] . The most common symptom of NCLB is necrotic green-gray lesions on leaves with a length range from 2 to 14 cm, which could lead to 10–40% grain yield losses in severe cases [8] .…”
Section: Introductionmentioning
confidence: 99%